The Influence of Brand Experience and Perception Quality on Brand Loyalty Mediated by Brand Trust (Empirical Study: Mixue Consumers in Jakarta) - Angeline, Gabriela (Pelopor Publikasi Akademika, 2023)
The purpose of this study was to analyze the effect of brand experience and perceived quality on brand loyalty mediated by brand trust (Empirical Study: Mixed Consumers in Jakarta). This research is a type of quantitative research by collecting data from 127 respondents using a questionnaire distributed online with a Likert scale. Data analysis using PLS-SEM with SmartPLS 3.0 software. The research results obtained from this study are brand experience has a significant effect on brand loyalty. Other results prove that perceived quality has a significant effect on brand loyalty, brand experience has a significant effect on brand trust, perceived quality has a significant effect on brand trust and brand trust has a significant effect on brand loyalty.